Glycine and GABAA receptors mediate tonic and phasic inhibitory processes that contribute to prepulse inhibition in the goldfish startle network - Curtin, Paul C. P.; Preuss, Thomas (Frontiers in Neural Circuits, 2015)
Prepulse inhibition (PPI) is understood as a sensorimotor gating process that attenuates sensory flow to the startle pathway during early stages (20–1000 ms) of information processing. Here, we applied in vivo electrophysiology and pharmacology to determine if PPI is mediated by glycine receptors (GlyRs) and/or GABAA receptors (GABAARs) in the goldfish auditory startle circuit. Specifically, we used selective antagonists to dissect the contributions of target receptors on sound-evoked postsynaptic potentials (PSPs) recorded in the neurons that initiate startle, the Mauthner-cells (M-cell). We found that strychnine, a GlyR antagonist, disrupted a fast-activated (5 ms) and rapidly (<50 ms) decaying (feed-forward) inhibitory process that contributes to PPI at 20 ms prepulse/pulse inter-stimulus intervals (ISI). Additionally we observed increases of the evoked postsynaptic potential (PSP) peak amplitude (+87.43 ± 21.53%, N = 9) and duration (+204 ± 48.91%, N = 9). In contrast, treatment with bicuculline, a GABAAR antagonist, caused a general reduction in PPI across all tested interstimulus intervals (ISIs) (20–500 ms). Bicuculline also increased PSP peak amplitude (+133.8 ± 10.3%, N = 5) and PSP duration (+284.95 ± 65.64%, N = 5). Treatment with either antagonist also tonically increased post-synaptic excitability in the M-cells, reflected by an increase in the magnitude of antidromically-evoked action potentials (APs) by 15.07 ± 3.21%, N = 7 and 16.23 ± 7.08%, N = 5 for strychnine and bicuculline, respectively. These results suggest that GABAARs and GlyRs are functionally segregated to short- and longer-lasting sound-evoked (phasic) inhibitory processes that contribute to PPI, with the mediation of tonic inhibition by both receptor systems being critical for gain control within the M-cell startle circuit.